Car parking is a clinical quality issue. (14th April 2015) - Gilbert, David
Abstract : In the latest of a monthly series in which patients and carers set learning points for readers, David Gilbert urges healthcare staff to think again about their role in improving clinical outcomes. For more information about the series, contact Rosamund Snow, patient editor, rsnow@bmj.com .